Educação para o cuidado, cuidando da formação: possibilidades da preceptoria em psicologia na formação em psicologia hospitalar - Bórnea, Vinícius (2021)
The preceptor is a relatively new character in the formation of psychologists in hospital psychology. This research, through an existential and hermeneutic phenomenology approach, explores the meanings involved in the experience of preceptors and of student-interns that have been through the experience of formation in hospital psychology internships with a preceptor present. One preceptor and six former students were invited to take part in reflexive interviews in order to describe such experiences. The interviews were recorded and transcripted, and then analyzed and divided into “Junctures of meaning” that express the meanings that were comprehended. The narrative from the interviews was related to the discussion proposed by Martin Heidegger on Care (Sorge). This research presents possibilities to support the role of preceptorship in hospital psychology as a device that acts directly in the education process of professionals and interns in the health area. These possibilities do not serve to create a replicable manual, but to point out paths, reflections and possibilities for understanding this complex phenomenon, which is still little studied in psychology and education